Some Notes on the Energy Metabolism of Gadus callarias and Gadus virens in Relation to Body Size - Mahhargo Suprapto (Institute for Research and Community Services (LPPM) ITB, 1972)
The present work of oxygen consumption in Gadus callarias and Gadus virens shows that there is a connection between the body size and the acclimation time required for reaching a